2008
DOI: 10.1029/2007gl032066
|View full text |Cite
|
Sign up to set email alerts
|

Multiple thermal fronts near the Patagonian shelf break

Abstract: [1] Eighteen year (1985 -2002) sea surface temperature (SST) data are used to study the intraseasonal variability of the Patagonian shelf break front (SBF) in the SW South Atlantic Ocean between 39°and 44°S. The cross-shelf break SST gradients reveal distinct, previously undocumented thermal fronts located both, offshore and inshore of the SBF. Throughout the year the main SBF, identified as a band of negative SST gradient maxima (relatively strong offshore temperature decrease), forms a persistent feature lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 24 publications
2
37
0
1
Order By: Relevance
“…The sub-Antarctic shelf ecosystem is occupied by waters of sub-Antarctic origin transported onto the Shelf by the western branch of the cold Falkland (Malvinas) Current that mix with shelf waters forming several oceanographic fronts in the Southern Patagonian Shelf (Acha et al, 2004). The eastern branch of the Falkland Current forms the long Falkland/Malvinas Current Front that runs along the Patagonian shelf break and slope and frames the Patagonian large marine ecosystem from east (Acha et al, 2004;Franco et al, 2008). The temperate shelf ecosystem lies within waters of subtropical origin, transported onto the shelf by the Brazil Current and mixed with temperate shelf waters.…”
Section: Patagonian Large Marine Ecosystemmentioning
confidence: 99%
“…The sub-Antarctic shelf ecosystem is occupied by waters of sub-Antarctic origin transported onto the Shelf by the western branch of the cold Falkland (Malvinas) Current that mix with shelf waters forming several oceanographic fronts in the Southern Patagonian Shelf (Acha et al, 2004). The eastern branch of the Falkland Current forms the long Falkland/Malvinas Current Front that runs along the Patagonian shelf break and slope and frames the Patagonian large marine ecosystem from east (Acha et al, 2004;Franco et al, 2008). The temperate shelf ecosystem lies within waters of subtropical origin, transported onto the shelf by the Brazil Current and mixed with temperate shelf waters.…”
Section: Patagonian Large Marine Ecosystemmentioning
confidence: 99%
“…A plausible explanation for the apparent seasonal modulation of high-frequency SSTa is the seasonal variation in the magnitude of the temperature gradient (∂T /∂x) across the shelf break front. The SST gradient is highest in austral summer and lowest in winter (Saraceno et al, 2004;Franco et al, 2008;Rivas and Pisoni, 2010).…”
Section: Non Seasonal Sea Surface Temperature Variabilitymentioning
confidence: 99%
“…9) have shown that the high SST gradient band observed along the western edge of the Malvinas Current between 39 and 44 • S closely follows the line of constant potential vorticity (f/H , where f is the Coriolis parameter and H is the bottom depth) equal to 2×10 −7 m −1 s −1 . More recently, Franco et al (2008) have suggested that the surface transition between shelf and Malvinas Current waters is organized as a series of distinct thermal fronts, each following lines of constant potential vorticity, except for the westernmost front located over the outer continental shelf, which is more variable. Variability of the inshore front is presumably due to reduced f/H gradients and a less pronounced topographic control of the flow in the outer shelf.…”
Section: Genesis Of Slope Water Intrusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equatorial currents (Firing 1987) might be dynamically related to the midlatitude, multiple zonal jets through instabilities of large-scale waves (e.g., Hua et al 2008). Multiple-jet zonation of currents is also observed on continental slopes (Franco et al 2008), suggesting the important role for the topographic b effect. Finally, vigorous research on zonal jets is carried out by the plasma physics community-many aspects of this effort have geophysical counterparts; a comprehensive review of the subject is in Diamond et al (2005).…”
Section: A Backgroundmentioning
confidence: 99%